Implementación de un Sistema de Producción y control de calidad en los procesos productivos para la cooperativa de producción agrícola comunitaria granos Andinos San Miguel de Chugchilán “Coopgranach”. - Chaluisa Pastuña, Ángel Neptalí (2021)
The “Cooperativa de Producción Agrícola Comunitaria Granos Andinos San Miguel de Chugchilán Coopgranach” is an associated entity of farmers, where it is dedicated to the collection, processing and packaging of Andean lupine, so it is necessary to improve productivity and customer service, so that the information found there is vulnerable to loss, improper use and lack of integrity, generating loss of time in administrative processes and in customer service. The purpose of this research is to optimize the management of production processes and quality control, which will be able to streamline the procedure and automate the proper management and control of production processes in the Cooperativa de Producción Agricola Comunitaria Granos Andinos San Miguel de Chugchilán "COOPGRANACH", which produces, transforms and markets lupines, as well as Andean grains, in such a way that the time in the production management processes will decrease. It is proposed to improve this management through the development and implementation of a computer system that will help optimize the required records. It consists of the analysis, development and implementation of a management software, with the aim of providing digital hosting and managing the production processes of information in the management of that entity, managing to omit the usual practices that they have been carrying out so far.